MANEJEMEN BENCANA TANAH LONGSOR KABUPATEN AGAM PROVINSI SUMATERA BARAT - Abimayu Putra Udaya; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Disaster management is the management of natural and non-natural disasters to minimize the impact of disasters that are generated in an area. There are various kinds of disasters in Indonesia such as earthquakes, tsunamis, landslides, fires, floods, and others. In Agam Regency itself has a complex disaster from other districts in West Sumatra Province. And the most disasters are landslides, this is because the topography and natural structure in Agam Regency have many hills. The purpose of this study was to determine the management of landslides in the Agam District of West Sumatra Province and the factors that hampered the management of the landslides in the Agam District of West Sumatra Province. The technique used is snowball sampling with the type of qualitative research using a descriptive approach and the data needed both primary and secondary data obtained by observation, interviews and documentation. Furthermore, the management of the landslide disaster has proceeded well, but it has been blocked due to factors such as budgeting, limited human resources, coordination with related agencies, and community relations with BPBD.Keyword Disaster Management, Landslide, BPBD